Low plasma level of insulin-like growth factor-I (IGF-I) is a risk factor for multibacillary type of leprosy - Luh Mas Rusyati; Made Swastika Adiguna; Indra Teguh Wiryo (Bali Dermatology and Venereology Journal, 2018)
Introduction: Leprosy is one of infectious diseases with complex issues. Previous study showed poverty, malnutrition, lack of proper food and nutrient intake, as well as low income. Recently, many studies reported insulin-like growth factor-I (IGF-I) as excellent nutrient marker.Objective: This study aims to prove that low plasma level of insulin-like growth factor-I is a risk factor for multibacillary type of leprosy. Material and methods: This case-control study design involved 38 patients with leprosy subjects as cases and 38 control subjects. The sample collection is done by consecutive sampling and has fulfilled the inclusion and exclusion criteria which matched by age and gender in Dermatology and Venereology Outpatient clinic of Sanglah General Hosptital. The collected data was analyzed using SPSS version 23.0 with Pearson Chi square test to obtain Odds Ratio. Results: This study showed that IGF-I plasma levels in the case group were significantly lower than the control group (p<0.05) with Odds ratio for IGF-I plasma 34.61 (95% CI= 7.17-167.01, p<0.001)Conclusion: Low plasma level of insulin-like growth factor-I is a risk factor for multibacillary type of leprosy.